Secretome analysis revealed that cell wall remodeling and starch catabolism underlie the early stages of somatic embryogenesis in Pinus nigra - Pernis, Miroslav; Salaj, Terézia; Bellová, Jana; Danchenko, Maksym; Baráth, Peter; Klubicová, Katarína (Frontiers in Plant Science, 2023)
Somatic embryogenesis is an efficient mean for rapid micropropagation and preservation of the germplasm of valuable coniferous trees. Little is known about how the composition of secretome tracks down the level of embryogenic capacity. Unlike embryogenic tissue on solid medium, suspension cell cultures enable to study extracellular proteins secreted into a liquid cultivation medium, avoiding contamination from destructured cells. Here we present proteomic data of the secretome of Pinus nigra cell lines with contrasting embryogenic capacity, accounting for variability between genotypes. Our results showed that cell wall-related and carbohydrate-acting proteins were the most differentially accumulated. Peroxidases, extensin, α-amylase, plant basic secretory family protein (BSP) and basic secretory protease (S) were more abundant in the medium from the lines with high embryogenic capacity. On the contrary, the medium from the low embryogenic capacity cell lines contained a higher amount of polygalacturonases, hothead protein and expansin, which are generally associated with cell wall loosening or softening. These results corroborated the microscopic findings in cell lines with low embryogenic capacity -long suspensor cells without proper assembly. Furthermore, proteomic data were subsequently validated by peroxidase and amylase activity assays and hence we conclude that both tested enzyme activities can be considered potential markers of high embryogenic capacity.